Scouting for Huanglongbing (HLB; Citrus Greening) - Jamie D. Burrow; Stephen H. Futch; Tripti Vashisth; Timothy M. Spann (EDIS)
This illustrated trifold brochure is best viewed in pdf format. It highlights the purpose of scouting, frequency, methods, grove conditions, tagging suspect trees, scout responsibilities, safety concerns, diagnostics, and what to scout for. Includes contact information for UF/IFAS Extension citrus experts. It is a minor revision written by Jamie D. Burrow, Stephen H. Futch, Tripti Vashisth, and Timothy M. Spann, and published by the Horticultural Sciences Department, December 2019.